Carbon dynamics in Patagonian peatlands: are beavers transforming carbon sinks into net carbon sources? - (:unkn) unknown (My University, 2025)
Chilean Patagonian peatlands have behaved as carbon sinks during the past 18 000 years and currently represent a reservoir of ˜ 4.6 Gt of carbon. However, climate change and anthropogenic activities are currently disturbing the carbon dynamics in Patagonian peatlands, potentially transforming them from carbon sinks into net carbon sources. The introduction of beavers into Tierra del Fuego ca. 1946 is among the anthropogenic related disturbances affecting carbon dynamics in Patagonian peatlands. At the moment, beavers in the Chilean territory of Tierra del Fuego have impacted > 54 000 ha of forests, compromising ˜ 9 million tons of native forest carbon stock. However, the impact of beaver activity on the carbon dynamics of Patagonian peatlands in the context of climate change has not been quantitatively estimated. This severely limits the capacity of Chile to include peatlands as part of its Nationally Determined Contributions to achieve carbon neutrality by 2050. For this reason, the main objective of this project is to provide a quantitative understanding of the impact of beaver activity (e.g. dam and channels construction) on the capacity of peatlands to accumulate and release carbon into the atmosphere in Patagonia. I will test the hypothesis that, the construction of beaver dams in conjunction with the predicted changes in climate for Patagonia will lead to a significant decrease in the level of the water table in peatlands, increasing carbon loss and triggering peat subsidence. To test this hypothesis, I will address the following objectives: i) Measure the spatial and temporal fluctuations of the water table and greenhouse gas emissions (CO2 and CH4) in Patagonian peatlands disturbed by beaver activity; ii) Evaluate the interaction between water table height, temperature, and peat composition as drivers of carbon dynamics in peatlands disturbed by beaver activity; iii) Assess the spatial and temporal changes in subsidence in Patagonian peatlands disturbed by beaver activity through the analysis of satellite imagery; and iv) Define if fossil peat layers contribute to CO2 and CH4 emission, and dissolved organic carbon (DOC) export in peatlands disturbed by beaver activity through isotopic characterization. In order to accomplish these objectives, the project will have a duration of three years, during which I will conduct a series of in situ and ex situ experiments, and will use remote sensing approaches. The experiments will be conducted in the three areas of Patagonia where beaver activity has impacted the most: Tierra del Fuego, Navarino Island, and Continental Magallanes. The study sites in each area will include pristine peatlands and peatlands disturbed by beaver activity. To achieve objective i), I will install autonomous water level sensors in the study sites, measure hydraulic conductivity through the peat profile, and gather the meteorological data available for each research area. In addition, I will measure CO2 and CH4 fluxes in situ using the static chamber technique and I will quantify CO2 and CH4 concentrations in situ thorough the peat profile. Addressing objective ii) will require conducting respirometric assays at different temperatures and under oxic-anoxic conditions using samples from the peat stratigraphic profile from each site. The respirometric analysis will provide information about the CO2 and CH4 production rates under different potential climate scenarios. Peat cores will be physico-chemical and molecularly characterized, including gravimetric analyses (bulk density, loss on ignition), total carbon, total organic carbon, total nitrogen, total phosphorus, total sulfur, tetramethylammonium-pyrolysis-gas chromatography-mass spectrometry, Fourier-transform infrared spectroscopy, and stable isotopic analysis (13C/12C). I will also evaluate changes on the Recent Rate of Carbon Accumulation using 210Pb and Long Term Rate of Carbon Accumulation using 14C from basal peat. Net Carbon Exchange (i.e., gross primary productivity minus the ecosystem respiration) will also be measured allowing quantifying the current capacity of Patagonian peatlands as carbon sinks. To address objective iii) I will use Sentinel-1 InSAR (Interferometric Synthetic Aperture Radar) time series data (2014-2022) to estimate peat subsidence and water table fluctuations in conjunction with cloud-free optical imagery. Objective iv) will require the isotopic analysis of 13C/12C and 14C in peat, CO2, CH4, and DOC in the water streams. The completion of the objectives will allow testing the proposed hypothesis, developing a quantitative estimation of the impact of beaver activity on the carbon sink capacity of Patagonian peatlands and defining if beavers have triggered the loss of the carbon stocks accumulated as fossil peat. Additionally, the information obtained from this project will provide a base line for CO2 and CH4 emissions from Patagonian peatlands under distinct temperature and water table level scenarios; and the remote sensing approach will deliver an alternative tool to monitor spatial and temporal shifts in peatlands hydrology, extent, and carbon stock. Together, the outcomes from this project will help improving the current estimations of land cover, carbon emissions, and carbon stocks of Patagonian peatlands disturbed by beaver activity.
Keywords: metano; gases de efecto invernadero; cambio climatico; calentamiento global; turberas; carbono; castores; especies invasivas